The Effectiveness of the Implementation of Cash Flow System Model to Enhance the Ability to Write Cash Flow Reports - Ni Luh Gede Erni Sulindawati (International Journal of Social Science and Business, 2019)
This study aimed at finding out the effectiveness of the cash flow system model that has been validated from experts in a focus group discussion (FGD).  This study used  the continuation off the  stages in the development method of the previous study, that is, the implementation stage.  At this implement stage the cash flow system teaching model was tested in a class of students who programed financial accounting course, one of whose learning achievements was  the ability to write cash flow reports. Data collection techniques carried out by means of observation, interview, documentation, and a learning achievement test. The study used the quantitative descriptive analysis  technique  by measuring  the students’ learning achievement  as seen from the scores they obtained in the teaching process of cash flow report writing sessions. This study was done based on the scores obtained in the process of the writing of cash flow reports. The assessment was done based on the scores obtained for the assessment process of attitude, participation, assignment and learning achievement as seen from the evaluation of the products produced. From the implementation it was found out that the students’ learning achievement in writing cash flow reports  in terms of  attitude, participation, and product  evaluation respectively  fell into a very good category.  Hence, the cash flow system model is effective for use in the teaching process